El exilio de Ramón Alesón Alonso de Tejada : Experienca liberal de un emigrado en Londres (1823-1826) - Viguera Ruiz, Rebeca (Edwin Mellen Press, 2011)
This book is an important contribution to the history of Spanish liberalism, as well as a study of the exile communities of 19th century Europe, detailing the political encounters and exchanges that were generated. Many exiles left their countries in the aftermath of failed uprisings, when attempts to establish forms of constitutional and representative government for national independence resulted in reactionary backlash and foreign invasion. Their preferred destination was the United Kingdom, often settling in London. London was a cosmopolitan metropolis, famous for its toleration and openne.